The Interplay of Servant Leader and Interpersonal Trust in Predicting Employee-Based Brand Equity: Moderating Role of Ethical Work Climate - Zhang, Shaoting; Guo, Shaohua (Frontiers in Psychology, 2022)
Although servant leadership may be equipped to provide a leadership model which addresses the issues of the modern workforce, however little literate is available regarding relationship of servant leadership and employee brand based equity. This study contends to address this gap for which data has been collected from the service industry under cross sectional research design by distributing 410 questionnaires among the participants, out of which 337 questionnaires were received back. After discarding the partially filled and incomplete responses the useable responses were 314. Data has been analyzed through the Smart PLS by applying Structural Equation Modeling technique. Results indicate that servant leadership increased the employee brand based equity directly and through the mediating role of interpersonal trust. However, moderating role of ethical work climate has not been established in this study.